Effect of soil types on erosion - Siti Mariam , Ramli (2012)
Slope erosion has been a global phenomenon over the century. However, only few further researches have been discovered in this area. Soil erosion is the process involving detachment and transportation of soil from the soil origin. Soil erosion is one form of soil degradation along with soil compaction, low organic matter, and loss of soil structure, poor internal drainage, and soil acidity problems. There is some factor that might cause erosion. One of the factors is the type of soil and its particle size. A study using soil erosion modeling was conducted to determine how effective the type of soil will influenced erosion. The size of the test bed tray is 400mm in wide, 100mm of height and 800mm length. Each test will contain different percentage of soil. There are total 3 mixed of soil in this test. First sample will use 10% of silty clay and 90 % of sand from the total weight of the mixed. Then for second sample will use 70 % of silty clay and 30 % of sand. For the last sample will use 50% of silty clay and sand. Each test will run approximately 15 minutes. Generally the results showed that the erosion increased when soil particle size is increased. From the observation of each test, then the erosion index is calculated and determined.